Pirate spacecat attack - Stilton, Geronimo (Stilton, Geronimo. Spacemice, 2017)
Geronimo Stiltonix takes MouseStar 1's broken computer to a distant planet to be repaired by a brilliant inventor, but pirate spacecats attack and steal the device, and the spacemice must retrieve it before the machine can be turned against them.